Alimentação saudável e aleitamento materno: um estudo em gestantes do Espírito Santo - Prado, Camila Bruneli do (2022)
INTRODUCTION: One of the main actions of prenatal care is the encouragement of healthy eating habits and the encouragement of breastfeeding (BF). Knowing the gaps found in promoting healthy eating during pregnancy and encouraging the BF process, also seen in the indicators, this study is justified. OBJECTIVE: To assess adherence to the ten steps of healthy eating and the knowledge of pregnant women about breastfeeding. METHODOLOGY: This is a cross-sectional epidemiological study with pregnant women living in Espírito Santo. Pregnant women under 20 years of age were excluded from the study. The data collection tool was developed on the Research Electronic Data Capture (REDCap) platform and shared through a survey on social networks. The instruments for data collection included questions related to personal data, socioeconomic characteristics, prenatal care and evaluation of the “Ten steps to healthy eating in prenatal care”, adapted from the Ministry of Health, and knowledge about the “Importance of Breastfeeding”. Maternal”. To analyze and evaluate the results, the Praise-Orient-Recommend (EOR) system was used. IBM SPSS Statistics for Windows, version 22.0 (Armonk, NY: IBM Corp) was used for statistical analysis. RESULTS: As the main research findings regarding adherence to the ten steps for healthy eating, most pregnant women reported adherence to 3 to 5 steps (78.5%), fitting into the Guide category. It was observed that receiving nutritional guidance during prenatal care increased adherence to step 4 (OR: 1.99; 95%CI: 1.26-3.15), step 5 (OR: 2.02; 95%CI: 1, 26-3.24) and step 9 (OR: 1.66; 95%CI: 1.66-2.58). In the investigation of the knowledge of pregnant women about breastfeeding, the majority (63.6%) reported that they did not receive prenatal guidance on the subject, but 81% knew from two to nine topics related to the theme. Among the most well-known topics are the topics related to “baby suction and increased milk production” (n=111; 94.1%) and the “ideal time of exclusive breastfeeding” (n=111; 94.1%). The restriction to breastfeed and be HIV/HTLV positive (n=59; 51.7%) was the least known topic by pregnant women. FINAL CONSIDERATIONS: The findings indicate that prenatal guidelines directly influence pregnant women's food choices and knowledge about the breastfeeding process. Thus, public policies that interfere in the modifiable factors associated, among them, implementation of health education in prenatal care are necessary.